Changing Substance Abuse Through Health and Social Systems
XIX, 260 p.
Keywords: In both developed nations and the developing world, there is a clear trend towards addressing alcohol, tobacco, and other drug problems through health and social services. There are several persuasive arguments for this shift beyond pure economics, which include comorbidity, cost effectiveness, coordination of care and effectiveness. This is the first volume to pull together effective methods that can be used for addressing substance abuse through health and social service systems. It also integrates interventions for a range of drugs of abuse, rather than focusing on only one (such as alcohol). The book's international perspective also makes this a unique contribution to the existing literature.